2019
DOI: 10.1002/eji.201847857
|View full text |Cite
|
Sign up to set email alerts
|

Translational repression of Ccl5 and Cxcl10 by 4E‐BP1 and 4E‐BP2 restrains the ability of mouse macrophages to induce migration of activated T cells

Abstract: Signaling through the mechanistic target of rapamycin complex 1 (mTORC1) is a major regulatory node of pro‐inflammatory mediator production by macrophages (MΦs). However, it is still unclear whether such regulation relies on selective translational control by two of the main mTORC1 effectors, the eIF4E‐binding proteins 1 and 2 (4E‐BP1/2). By comparing translational efficiencies of immune‐related transcripts of MΦs from WT and 4E‐BP1/2 double‐KO (DKO) mice, we found that translation of mRNAs encoding the pro‐in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
1
15
0
1
Order By: Relevance
“…A number of prior studies showed the requirement of mTOR for chemokine induction in some immune cell subsets, such as monocytes and macrophages (Jin and Zhao, 2020;Lin et al, 2014;William et al, 2019). Therefore, we investigated whether mTOR was similarly involved in chemokine induction in breast cancer cells treated with CDK4/6i.…”
Section: Cdk4/6i Inhibits Expression Of Cell Cycle Mediators While Promoting Mtor Activitymentioning
confidence: 96%
“…A number of prior studies showed the requirement of mTOR for chemokine induction in some immune cell subsets, such as monocytes and macrophages (Jin and Zhao, 2020;Lin et al, 2014;William et al, 2019). Therefore, we investigated whether mTOR was similarly involved in chemokine induction in breast cancer cells treated with CDK4/6i.…”
Section: Cdk4/6i Inhibits Expression Of Cell Cycle Mediators While Promoting Mtor Activitymentioning
confidence: 96%
“…This is because there are clear limitations of the enteroid model which do not represent the complex interplay for immune and stromal cells that would be found in vivo . Also, it is known that Cxcl10 transcription depends on protein synthesis ( 86 , 87 ) and on additional transcription factors, such as activator protein 1 (AP-1) ( 87 ) and key transcriptional repressors 4E-BP1/2 ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among post-transcriptional mechanisms, transcript-selective changes in translational efficiencies enable cells to swiftly remodel their proteomes in response to environmental cues without requiring de novo mRNA synthesis [10][11][12][13]. In eukaryotes, translational efficiency is mainly regulated at the initiation step when ribosomes are recruited to the mRNA [14].…”
Section: Introductionmentioning
confidence: 99%